Pengolahan Ikan Sebagai Nugget Untuk Pencegahan Stunting di Desa Obel-Obel, Kecamatan Sambelia, Kabupaten Lombok Timur - Fania Rahman; Nazri Al Ayyubi; Muhamad Taufik Hidayat; Ahmad Hasa Fahrurozi; Annisa Aprilia; Vini Vionadhia Indriyani; Citra Wulandari; Soleha Az Zahra; Serlu Ayu Cahyani; Salsabila Mustaan; Muhammad Yusup (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time due to the provision of food that does not match nutritional needs. The problem of stunting occurs in various villages, one of which is Obel-obel Village. Obel-obel Village is one of the villages in Sambelia District, East Lombok Regency, West Nusa Tenggara Province. The problem of stunting in Obel-obel Village occurs in several families. This village is also a village that has high food potential, but the processing process is said to be lacking, therefore the Obel-obel Village KKN team tried a new variation, namely processing marine fish nuggets to prevent stunting.